Influência da vermiculita expandida na resistência à compressão e reologia de pastas cimentantes de poços de petróleo - Lima, Fernando Antonio de Melo (2009)
Several problems related to the loss of hydraulic seal in oilwells, causing gas migration and/or contamination of the production zone by water, have been reported. The loss of the hydraulic seal is a consequence of cracks which can be occasioned either by the invasion of gas during the wait on cement or by the expansion of the casing causing the fracture of the cement sheath. In case of the pressure of the formation is higher than the pressure in the annulus, gas can migrate into the slurry and form microannulus, which are channels where gas migrates after the cement is set. Cracks can be also occasioned by the fracture of the cement sheath when it does not withstand the thermal and dynamic loads. In reservoirs where the oil is heavy, steam water injection operation is required in order to get the oil flowing. This operation increases the temperature of the casing, and then it expands and causes the fracture of the cement sheath in the annulus. When the failures on the cement are detected, remedial cementing is required, which raise costs caused by the interventions. Once the use of cement in the construction civil sector is older than its use in the petroleum sector, it is common to bring technologies and solutions from the civil construction and apply them on the petroleum area. In this context, vermiculite, a mineral-clay widely encountered in Brazil, has been used, on its exfoliated form, in the civil construction, especially on the manufacture of lights and fireproof concretes with excellent thermal and acoustical properties. It has already been reported in scientific journals, studies of the addition of exfoliated vermiculite in Portland cements revealing good properties related to oilwell cementing operations. Thus, this study aimed to study the rheological behavior, thickening time, stability and compressive strength of the slurries made of Portland cement and exfoliated vermiculite in 5 different compositions, at room temperature and heated. The results showed that the compressive strength decreased with the addition of exfoliated vermiculite, however the values are still allowed for oiwell cementing operations. The thickening time of the slurry with no exfoliated vermiculite was 120 min and the thickening time of the slurry with 12 % of exfoliated vermiculite was 98 min. The stability and the rheological behavior of the slurries revealed that the exfoliated vermiculite absorbed water and therefore increased the viscosity of the slurries, even though increasing the factor cement-water. The stability experiment carried out at 133 ºF showed that, there was neither sedimentation nor reduction of the volume of the cement for the slurry with 12 % of exfoliated vermiculite. Thus, the addition of exfoliated vermiculite accelerates the set time of the cement and gives it a small shrinkage during the wait on cement, which are important to prevent gas migration